Definitive therapy of colonic angioectasia by submucosal coagulation - Sriram, Nagaraj; Bar-Yishay, Iddo; Kumarasinghe, Priyanthi; Yusoff, Ian; Segarajasingam, Dev; Bourke, Michael J.; Raftopoulos, Spiro (Endoscopy International Open, 2019)
Background and study aims Colonic angioectasia are the most common vascular lesions in the gastrointestinal tract and are among the most common causes for chronic or recurrent lower gastrointestinal bleeding. Endoscopic treatment involves a variety of techniques, all of which focus on destruction of the mucosal abnormality. However, recurrent bleeding after endoscopic treatment is common, with more than one treatment frequently necessary. We report a technique for definitive treatment of colonic angioectasia by targeting the feeding submucosal vessel. Patients and methods Analogous to endoscopic mucosal resection, a submucosal injection is made beneath the target lesion which is then removed by electrocautery snare resection of the mucosal lesion. The exposed feeding vessel is then destroyed by application of coagulation current. The resection defect is closed by clips. Results Six patients with a total of 14 colonic angioectasia were treated over the study period. All lesions were destroyed without adverse events. Conclusion Elevation, hot snare resection and coagulation (ESC) of the visible vessel for treating colonic angioectasia appears safe and effective. Larger prospective comparative studies are required to assess its specific role.